Cultural Landscape and Heritage as an Opportunity for Territorial Resilience—The Case of the Border Between Castile and Leon and Cantabria - María Teresa Pérez Cano; Ainhoa Maruri Arana (Land)
The loss of functions in Spanish rural areas has triggered territorial inequalities and injustices in a highly complex geographical environment. After the COVID-19 pandemic and in a context of overpopulation in large cities, the rural area emerged as a space of opportunity for more sustainable territorial rebalancing. Despite the evident tendency towards their population emptying, they are places endowed with their own qualities and specific values, currently in danger, especially in border areas between the regions, which are far from centralised nuclei and generate conflicts due to the transfer of powers to them from the State. Among these values is cultural heritage, the safeguarding and enrichment of which depends on the balance between the landscape and the society that hosts it. This work focuses on access to archaeological sites—an important form of heritage prior to the establishment of actual regional divisions, in the depopulated frontier between Cantabria and Castile and Leon—whose potential is presented by their intrinsic relationship with the territory and their ability to identify historical landscapes, advocating for future sustainability on a territorial scale. With all of the above, a cultural landscape delimitation is proposed between both regions that share common characteristics and problems, promoting synergies and territorial readings by analysing the territorial assets of these interior areas so that their potential is not diminished.